Satellite TVRO system reception under tropical weather conditions effects - Ibrahim, Raed A. R.; Al-Khateeb, Khalid A. Saeed (2005)
TVRO systems suffers from the tropical weather conditions effects. This paper evaluate the system based on its effects of that conditions. This paper presents a Satellite TVRO system reception with regard to various weather conditions effects such as day time, night time as well as clear sky and rain sky conditions have been highlighted. The Geo arc that has been derived from such system represent the application of TVRO. The TVRO structures a Geo-arc formation and formulation in terms of satellite signals losses.